Management of large mandibular ameloblastoma: a case report - Rahman, Md Mizanur; Uddin, Wares; Uddin, Main; Sarwar, AFM (Journal of Chittagong Medical College Teachers’ Association, 2011)
Keywords: ameloblastoma; hemimandibulectomy; disarticulation DOI: http://dx.doi.org/10.3329/jcmcta.v22i1.9112 JCMCTA 2011; 22(1): 39-42